Jaguariba wiersemana gen. nov. et sp. nov., an Early Cretaceous member of crown group Nymphaeales (Nymphaeaceae) from northern Gondwana. Issue 1 (1st February 2013) - Coiffard, Clément; Mohr, Barbara A.R.; Bernardes-de-Oliveira, Mary E.C.
Abstract: Morphology and anatomy of a fossil nymphaealean plant, Jaguariba wiersemana gen. nov. et sp. nov. from the late Early Cretaceous of northeastern Brazil, and extant aquatic flowering plants are comparatively studied. Characteristic features indicate that Jaguariba gen. nov. is a member of Nymphaeaceae, and may belong to Nymphaeoideae. The occurrence of both Nymphaeaceae and Cabombaceae (e.g., Pluricarpellatia peltata) in the Lower Cretaceous contradicts recent molecular dating implying a Late Cretaceous–Early Tertiary divergence for those families. Furthermore, the morphology of the fossil and sedimentologic and taphonomic data indicate that Jaguariba gen. nov. had an aquatic ecology similar to living Nymphaeaceae. Thus the taxon was part of the aquatic vegetation of the Crato lake in association with Pluricarpellatia peltata, an earlier described cabombaceaen aquatic angiosperm.